Role of the Epipapillary Membrane in Maculopathy Associated with Cavitary Optic Disc Anomalies: Morphology, Surgical Outcomes, and Histopathology - Atsushi Tanaka; Wataru Saito; Satoru Kase; Kan Ishijima; Kousuke Noda; Susumu Ishida (Journal of Ophthalmology)
Purpose. To evaluate the surgical outcomes of pars plana vitrectomy (PPV) with epipapillary membrane removal in patients with maculopathy associated with cavitary optic disc anomalies. Methods. Eight patients (8 eyes) with cavitary optic disc anomaly-associated maculopathy who underwent PPV with epipapillary membrane removal were retrospectively reviewed. The best-corrected visual acuity (BCVA) and macular and papillary morphologies using enhanced depth imaging optical coherence tomography (EDI-OCT) were evaluated before and after treatment. Immunohistochemistry for an intraoperatively excised epipapillary membrane tissue was also performed. Results. Before surgery, EDI-OCT revealed that epipapillary membrane was observed in all patients. Retinoschisis was resolved with no recurrence in all patients following vitrectomy regardless of a disease type or the presence or absence of preoperative posterior vitreous detachment. The mean final BCVA and central retinal thickness significantly improved compared with pretreatment values (P=0.008 and 0.004, resp.). Immunoreactivity for S100 protein and glial fibrillary acidic protein, markers of astrocytes, was positive in the resected membrane tissues. Conclusions. These results suggest that epipapillary membrane is involved in the pathogenesis of some patients with cavitary optic disc anomaly-associated maculopathy as well as posterior hyaloid membrane. PPV with epipapillary membrane removal may be a useful treatment option for this maculopathy. This trial is registered with UMIN000011123.